PENGARUH KEPEMILIKAN INSTITUSIONAL, KEBIJAKAN DIVIDEN DAN RASIO KEUANGAN TERHADAP NILAI PERUSAHAAN - Benita, Jessica; Tjhai, Fung Jin (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2025)
This study aims to analyze the effect of dividend policy, investment decisions, leverage, profitability, company size, liquidity, sales growth, institutional ownership, and activity ratio on firm value. This study uses a sample of all manufacturing sector companies listed on the Indonesia Stock Exchange (IDX) during the 2021-2023 period with 44 manufacturing sector companies as samples in this study. Through purposive sampling method and analyzed with multiple linear regression. The results showed that leverage, profitability, liquidity, and institutional ownership have a positive effect on firm value. The higher leverage shows that the company is able to manage debt effectively so it can attract shareholder attention. High profitability provides a positive signal to investors regarding the profits generated by the company. A high level of liquidity indicates that the company is able to finance its short-term debt so this may increase the value of the company. Institutional ownership that increases reflects the strict supervision of investors so it can prevent management's opportunistic behavior and increase firm value. On the other hand, dividend policy, investment decisions, firm size, sales growth, and activity ratio have no effect on firm value.